The Major Factors of Consolidation and Islamization of the Turkic-Speaking Population of Western Siberia in the 16th–19th centuries » - S.F. Tataurov (Золотоордынское обозрение)
The article shows the importance of archaeological materials, particularly of funerary complexes, for both analyzing the process of formation of the Siberian Tatars in the 16th–17th centuries and studying the features of the development of Islam in Siberia. The author examines the problem of consolidation of the Turkic-speaking population of the forest-steppe zone of Western Siberia in the second millennium AD, which was expressed in the formation of a common cultural, linguistic, and religious space. The author considers the reasons for duration of this process, analyzes the factors that impeded or facilitated the convergence of certain ethnic groups, the level of socio-economic relations, political developments in these regions. The article shows the importance of the Siberian Khanate as a state and ideological unification of the Turkic-speaking population of Western Siberia, as the main unifying factor in the formation of this ethnic group. The author emphasizes the role of the Russian administration, its action for the creation of new Siberian administrative-territorial system, for the spread of Orthodox Christianity, etc. Particular attention is paid to the process of Islamization of the population already living in the framework of the Russian State after the arrival of Russians, to role in this process of the patrimonial Tatar nobility. As a result, we can construct the situation as follows. Influenced primarily by political (but not economic) developments, the Turkic-speaking population of Western Siberia was sufficient organized to the last third of the 16th century that is ready to the further rapprochement and transformation into single ethnic group. The weakness of social and economic relations did not allow to develop this convergence. Process of consolidation already began to develop in other conditions – after annexation of Western Siberia by the Russian State – in the 17th–19th centuries. The Tatar nobility and Muslim population migrated from Central Asia and the Lower Volga region, played a key role in this process and Islamization of the entire Turkic-speaking population became a crucial factor. This article only underlines major factors of this process. The whole complex of historical, ethnographic, archaeological, and genetic research is needed to fully explore the history of the formation of the Siberian Tatars and defining its basic chronological stages and driving forces.